Gold nanoparticle encoded with marigold (Tagetes erecta L.) suppressed hyperglycemia -induced senescence in retinal pigment epithelium via suppression of lipid peroxidation - Sun Young Park; Kangmin Park; Jin-Woo Oh; Geuntae Park (Arabian Journal of Chemistry, 2023)
This paper presents a simple and environmentally friendly method for synthesizing Tagetes erecta L. gold nanoparticles (TE-GNPs) using an aqueous extract of Tagetes erecta L. (TE). The TE extract serves as a reducing and stabilizing agent, and its antioxidant activity is evaluated using 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays. The TE extract exhibits significant DPPH and ABTS radical scavenging activities, indicating its strong antioxidative properties attributed to various antioxidant compounds. TE-GNPs are successfully synthesized by incubating the TE extract with a chloroauric acid solution, resulting in a color change from light yellow to ruby red. UV–Vis spectroscopy confirms the synthesis of TE-GNPs, evidenced by a characteristic absorption peak at approximately 524 nm, corresponding to the nanoparticles' surface plasmon resonance. Physicochemical characterization reveals that TE-GNPs possess nanoscale dimensions (28.9 ± 2.3 nm), stability (zeta potential of −31.5 ± 28), and a crystalline nature (validated via X-ray diffraction; XRD). Functional groups responsible for biosynthesis and stabilization are identified through Fourier transform infrared spectroscopy (FT-IR) analysis. high-resolution transmission electron microscopy (HR-TEM) images demonstrate the morphology, size, and dispersion of TE-GNPs, while selected area electron diffraction (SAED) patterns confirm their crystalline structures. Additionally, high-angle annular dark field (HAADF) imaging and energy-dispersive X-ray spectroscopy (EDX) spectroscopy verify the distribution and presence of gold in the TE-GNPs, respectively. Cytotoxicity assays confirm the biocompatibility of TE-GNPs. Furthermore, their potential in mitigating high glucose-induced cell death and oxidative stress in retinal pigment epithelial (RPE) cells is evaluated. Treatment with TE-GNPs restores the proliferation rate of RPE cells and reduces the proportion of apoptotic cells under high glucose conditions. TE-GNPs also decrease the high glucose-induced production of intracellular and mitochondrial reactive oxygen species. Markers of cellular senescence, including SA-β-galactosidase activity and lysosomal dysfunction, are attenuated by the TE-GNPs. Moreover, the TE-GNPs effectively reduce lipid accumulation and peroxidation in RPE cells exposed to high levels of glucose. These findings highlight the successful green synthesis of TE-GNPs using an aqueous extract of TE and underscore their desirable properties and anti-senescence effects.